Hydrostatic Pressure Increases the Catalytic Activity of Amyloid Fibril Enzymes. (29th August 2016) - Luong, Trung Quan; Erwin, Nelli; Neumann, Matthias; Schmidt, Andreas; Loos, Cornelia; Schmidt, Volker; Fändrich, Marcus; Winter, Roland
Abstract: We studied the combined effects of pressure (0.1–200 MPa) and temperature (22, 30, and 38 °C) on the catalytic activity of designed amyloid fibrils using a high‐pressure stopped‐flow system with rapid UV/Vis absorption detection. Complementary FT‐IR spectroscopic data revealed a remarkably high pressure and temperature stability of the fibrillar systems. High pressure enhances the esterase activity as a consequence of a negative activation volume at all temperatures (about −14 cm 3 mol −1 ). The enhancement is sustained in the whole temperature range covered, which allows a further acceleration of the enzymatic activity at high temperatures (activation energy 45–60 kJ mol −1 ). Our data reveal the great potential of using both pressure and temperature modulation to optimize the enzyme efficiency of catalytic amyloid fibrils.